“I ADMIRE AND RESPECT YOUR RELIGION BUT I MAY NOT PURSUE IT” Isaiah Berlin and Interfaith Dialogue - Dominador Bombongan Jr. (Journal of Dharma, 2012)
The twenty-first century world is increasingly becoming “multiethnic, multicultural and multireligious.” In this unique and complex condition the question of negotiating and dealing with various ethnicities, cultures and religions becomes more acute and pressing. Hence, one is bound to look for fruitful and productive ways of navigating through the meandering maze of this difficult yet challenging context. In this modest article we look at Isaiah Berlin’s idea of value pluralism and how this would help us respond creatively to the vexing question particularly of religious pluralism. We discover that in his view, the strict and uncritical adherence to and imposition of “dogmatically believed-in-schemes” of values and ideals usually result in destructive consequences to societies, cultures and peoples.Thus, instead of proposing the harmony of many diverse voices into one voice, he recognizes the cacophony of voices. Instead of supporting uniformity, conformity and unanimity in values, his is a celebration of diversity, difference and abundance.